Improving Viral Protease Inhibitors to Counter Drug Resistance. Issue 7 (July 2016) - Kurt Yilmaz, Nese; Swanstrom, Ronald; Schiffer, Celia A.
Abstract : Drug resistance is a major problem in health care, undermining therapy outcomes and necessitating novel approaches to drug design. Extensive studies on resistance to viral protease inhibitors, particularly those of HIV-1 and hepatitis C virus (HCV) protease, revealed a plethora of information on the structural and molecular mechanisms underlying resistance. These insights led to several strategies to improve viral protease inhibitors to counter resistance, such as exploiting the essential biological function and leveraging evolutionary constraints. Incorporation of these strategies into structure-based drug design can minimize vulnerability to resistance, not only for viral proteases but for other quickly evolving drug targets as well, toward designing inhibitors one step ahead of evolution to counter resistance with more intelligent and rational design. Trends: Viral proteases recognize substrates through a conserved shape, defining the substrate envelope. A variant that does not bind inhibitors efficiently but still processes substrates is resistant. Resistance mutations occur where inhibitors protrude outside of the substrate envelope. High-potency inhibitors that fit within the substrate envelope can avoid resistance. Resistance-avoiding strategies need to be included in structure-based drug design.